The effect of bending rigidity on polymers - Jia, Jiying; Li, Kunhe; Hofmann, Andreas; Heermann, Dieter W. (Macromolecular theory and simulations, 2019)
The conformations of chromatin are influenced by many factors. In the regulation of gene expression the bending rigidity of the chromatin polymer and its heterogeneity play an important role for the possible conformations. To elucidate this, the effect of bending rigidity as well as its heterogeneity on various polymer properties is investigated. In the context of chromatin organization, the contact probability is an important measure. It is analyzed whether there is any ambiguity in the definition of a contact. The results show that the contact probability does not depend on the range of contact in the limit of a large contour length between monomers. Further, the persistence length as a function of the bending rigidity is computed in the homogeneous and heterogeneous cases. The persistence length is systematically smaller in the heterogeneous case. Chromosomes are confined by each other in the nucleus and by looking at specific loci, the environment changes much more slowly than the local chromatin part. In conjunction with bending rigidity, polymers in rectangular confinements with several aspect ratios are simulated. Due to the spiraling behavior when the box size is small enough, an oscillation in the contact probability and the orientational correlation function is found.
Gesehen am 27.02.2020